2011
DOI: 10.1007/s12374-011-9185-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence Variation and Comparison of the 5S rRNA Sequences in Allium Species and their Chromosomal Distribution in Four Allium Species

Abstract: The gene structure and sequence diversity of 5S rRNA genes were analyzed in 13 Allium species. While the lengths and sequences of the coding gene segments were conserved, the spacers were highly variable and could be characterized as either short (213-404 bp) or long (384-486 bp) spacers. The short spacers were further classified into five subtypes (SS-I to SS-V) and the long spacers into four subtypes (LS-I to LS-IV). The short spacers were more conserved than were the long spacers. There was a sequence dupli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
3
6
0
1
Order By: Relevance
“…The number and localization of the rDNA sites that were obtained for A . fistulosum consents with most of the earlier reports (Kirov et al 2017 ; Lee et al 1999 ; Son et al 2012 ). However, Gernand et al ( 2007 ) reported additional one or four minor polymorphic sites of 35S rDNA on A .…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The number and localization of the rDNA sites that were obtained for A . fistulosum consents with most of the earlier reports (Kirov et al 2017 ; Lee et al 1999 ; Son et al 2012 ). However, Gernand et al ( 2007 ) reported additional one or four minor polymorphic sites of 35S rDNA on A .…”
Section: Discussionsupporting
confidence: 78%
“…Only two pairs of 5S rDNA sites were observed on the short arm of one chromosome pair in A . sativum , although earlier reports showed three pairs of sites of 5S rDNA in this species (one on the long arm and two on the short arm of the same chromosome pair; Lee et al 1999 ; Son et al 2012 ). Such phenomenon, the intraspecific polymorphisms in the rDNA sites number, has also been observed in many species including Amaranthus , Chenopodium , and Prospero (Jang et al 2013 ; Kolano et al 2013 ; Kolano et al 2015 ).…”
Section: Discussionmentioning
confidence: 65%
“…Jovan). This finding is similar to the expected ratio and is in line with reports involving other Allium genes [ 29 ]. Similar variability ratios were found for the other three accessions used in our alliinase variability analysis (Djambul1, Marhfeld, and Japo).…”
Section: Discussionsupporting
confidence: 93%
“…However, when inter-chromosome exchange is missing, 5S rDNA arrays located on different chromosomes could evolve independently. In other words, new variants formed via mutations and homogenization events could lead to development of chromosome-specific 5S rDNA arrays (Volkov et al, 2001;Son et al, 2012). Chromosome-specific arrays are also characteristic of polyploid species in which the outcome of concerted evolution depends on the frequency of genetic exchanges between homologous sequences on homoeologous chromosomes.…”
Section: Introductionmentioning
confidence: 99%